Kakovost življenja odraslih po zdravljenju skolioze - Mršnik, Marina (Rehabilitacija (Ljubljana), 2019)
Objective: Scoliosis is a three-dimensional torsional deformity of the spine, which affects 2-3% of the population, more often women. The most common form is adolescent idiopathic scoliosis (AIS). While medical doctors and other health care professionals are increasingly aware of the psychological issues faced by patients with scoliosis, only 5 % of studies on scoliosis included an aesthetic aspect, only 1.5 % a measure of health related quality of life (HRQL) and only 1 % assessed disability. In the literature there is considerable variation of the reported effects of scoliosis on quality of life. It also remains an open issue whether curve size, type of curve and type of treatment affect HRQL. The aim of our paper was to review the recent literature regarding quality of life of adults with idiopathic scoliosis who have been treated conservatively. Methods: The PubMed and Ovid databases were searched, using key words "idiopathic scoliosis" and "adults" in conjunction with "quality of life" or "long-term outcome". Results: We found 22 studies that fulfilled the inclusion criteria. The studies reveal that scoliosis negatively affects quality of life in adulthood. In addition, quality of life is influenced by gender, age, size of curve and type of curve, sagittal and frontal imbalance, and mode of treatment. Conclusion: Adults with scoliosis experience worse quality of life in comparison with healthy controls. It is therefore necessary to make diagnose early and prescribe treatment in order to prevent progression of scoliosis, so that surgical correction would not be needed or even to reduce the e curve size in order to preserve the quality of life in adulthood.
Keywords: Adult; adults; kakovost življenja; odrasli; quality of life; rehabilitation; Scoliosis; skolioza; SRS questionnaire; SRS vprašalnik; standard of living